Chemical cross-linking of Chlamydia trachomatis. - Birkelund, S (1988)
Purified elementary bodies (EBs) of Chlamydia trachomatis serovar L2 were analyzed by chemical cross-linking with disuccinimidyl selenodipropionate. The effect of the cross-linking was analyzed by immunoblotting sodium dodecyl sulfate-polyacrylamide gel electrophoresis-separated components which were reacted with monoclonal antibodies against major outer membrane protein (MOMP) and lipopolysaccharide (LPS). It was shown that in EBs, MOMP was cross-linked to the LPS component of the outer membrane. Migration analysis of the cross-linked components showed that with extensive cross-linking, most of the MOMP became cross-linked to LPS, changing the migration rate from 40 to 42.5 kilodaltons. A small fraction of MOMP associated with LPS was shown to be present in bands with migration rates of 100 and 110 kilodaltons. No association of MOMP or LPS to other proteins, or to dimer or multimer forms of MOMP without LPS, was observed. A totally different membrane structure must be present in reticulate bodies, since there, MOMP was so heavily cross-linked that it did not enter the polyacrylamide gel and thus became impossible to analyze. Furthermore, the monoclonal antibody, which reacted with LPS associated with MOMP in the cross-linked EBs, did not react with reticulate bodies.